Effect of Supervision of Employee Climate in CV. Akura Belitang East Oku - Gaeldeba Garaika (Komunitas Dosen Indonesia, 2020)
Problems faced by CV. Akura Belitang OKU Timur is how the influence of motivation on employee work discipline, while the purpose of this thesis is to determine the effect of motivation on employee work discipline. The hypothesis proposed is that motivation has a strong influence on employee work discipline in the CV. Akura Belitang Timur OKU. From the calculation results obtained figures r = 0.697. after consultation with conservative standards it turns out that 0697 lies between 0.600 - 0.799 which is included in the strong correlation. So it can be said that there is a strong influence between motivation on employee work discipline on the CV. Akura Belitang Timur OKU. Then to answer the hypothesis test proposed in the previous chapter has a relationship or not, then tested with a hypothesis test and obtained to = 2.916 then when connected with t value at a confidence level of 0 , 95 which means the error rate of 0.05 is t count greater from t table (2.916 greater than 1.833), the hypothesis proposed is to reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha).